Visual Literacy and Creative Ethics Challenges: A Conceptual Perspective on Plagiarism in the Digital Era and Art Education - Rahayu, Mardina; Sugiarto, Eko; Wibawanto, Wandah (Catharsis, 2025)
The rapid development of digital technology has revolutionized the field of visual arts, enabling ease of access, adaptation, and dissemination of artworks. However, this has also led to significant challenges, particularly plagiarism, which undermines the originality and ethical standards of creative processes. This study aims to develop a conceptual framework by integrating visual literacy and creative ethics as holistic approaches to prevent plagiarism in digital spaces, especially within art education. Through a literature review method, this research explores the interplay between visual literacyan essential skill for critically understanding and creating visual messages and creative ethics, which guide moral behavior in the artistic process. The findings emphasize the necessity of incorporating these two dimensions into art education curricula to build a more ethical, innovative, and responsible generation of creators. This study provides a theoretical foundation and practical recommendations for educators, policymakers, and the creative community to address plagiarism challenges effectively in the digital era.